Hepatic and Pancreatic manifestations of COVID-19 - Avinash H Rajanna,; Vaibhav S Bellary,; Arun Udayaraj, (Asian Journal of Medical Sciences, 2022)
Background: Since its first detection in November 2019, the outbreak of severe acute respiratory syndrome coronavirus 2 has influenced over 200 countries, areas or territories worldwide. The virus was initially thought to be a primary respiratory pathogen, but has been reported to have multisystem involvement, including cardiovascular, neurological and gastrointestinal manifestations. The manifestations of liver damage are usually mild and generally asymptomatic. While abdominal symptoms such as pain and diarrhoea are a known presentation, little is known about pancreatic injury as a complication of COVID-19 infection. Aims and Objectives: The aim of the study was to describe the abnormality in liver enzymes and pancreatic enzymes and to correlate it with the severity and outcome of COVID-19 patients. Materials and Methods: A total of 200 patients were enrolled during the study period from August-2020 to July-2021. Data were collected from case files of patients fulfilling the inclusion criteria. Results: A cross sectional study conducted among 200 patients showed that the mean aspartate transaminase and alanine transaminase values were 41.89±50.22U/L and 37.69±41.41U/L respectively and mean amylase and lipase levels were 97.77±126.42U/L and 90.34±127.76U/L. The percentage of transaminitis that was present in patients who were discharged was 29.41% when compared to those who died which was 53.33% and this difference is statistically significant(P=0.02).However, there was no statistically significant difference observed in patients with elevated pancreatic enzymes with their outcomes. C Conclusion: Hepatic injury is more commonly associated with an increased severity of the disease and also as a contributor for the greater mortality of the COVID-19 patients.